Pemantapan Materi Matematika Bagi Guru Matematika SMP/MTs Se-Kecamatan Kampar Kiri Provinsi Riau - Armis Armis; Atma Murni; Elfis Suanto; Putri Yuanita; Syofni Syofni (Jurnal Panjar: Pengabdian Bidang Pembelajaran, 2021)
This service activity aims to (1) improve the ability of teachers about mathematical material that contains ability of mathematical understanding, mathematical problem solving, or mathematical connections; (2) Providing knowledge to teachers about strategies of mathematical problem solving; and (3) drill teachers to solve mathematical problems that contain ability of mathematical understanding, mathematical problem solving, or mathematical connections. Activities carried out with a pattern of 40 hours @ 45 minutes, consisting of 18 hours face to face (first day and last day), and 22 hours of independent activity (2 weeks). In the independent activities the teacher is given the task of working on the questions at home and discussed again at the second meeting. The results of the analysis of the initial test answers obtained an average of 49.58 with the highest value of 90 and the lowest value of 15. Strengthening the material at the time of the training was more emphasized on materials not yet mastered by the teacher. After the training, the average teacher mastery increased at the final test to 75.56. It can be concluded that this community service activity can empower the community in Kampar Kiri sub-district especially the mastery of mathematics teachers in solving mathematical problems.